2019
DOI: 10.1016/j.jss.2018.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Donor GYY4137 Acts Through Endothelial Nitric Oxide to Protect Intestine in Murine Models of Necrotizing Enterocolitis and Intestinal Ischemia

Abstract: Background: Necrotizing enterocolitis (NEC) in premature infants is often a devastating surgical condition with poor outcomes. GYY4137 is a long-acting donor of hydrogen sulfide (H 2 S), a gasotransmitter that is protective against intestinal injury in experimental NEC, likely through protection against injury secondary to ischemia. We hypothesized that administration of GYY4137 would improve mesenteric perfusion, reduce intestinal injury, and reduce inflammatory responses in experimental NEC and ischemia-repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…NO belongs to the subfamily of endogenous gaseous signaling molecules, similar to hydrogen sulfide (H 2 S). Findings by other studies have also supported a role for NO and H 2 S to protect the intestine against the development of NEC by increasing microvascular blood flow via vasodilation 15 , 16 . These findings suggest that promoting sufficient intestinal blood flow in the immature intestine could prevent mucosal damage and improve the outcome of NEC.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…NO belongs to the subfamily of endogenous gaseous signaling molecules, similar to hydrogen sulfide (H 2 S). Findings by other studies have also supported a role for NO and H 2 S to protect the intestine against the development of NEC by increasing microvascular blood flow via vasodilation 15 , 16 . These findings suggest that promoting sufficient intestinal blood flow in the immature intestine could prevent mucosal damage and improve the outcome of NEC.…”
Section: Introductionmentioning
confidence: 74%
“…To explore the role of vasodilation and enhanced intestinal perfusion in the protective effects of RIC, we used chemical inhibitors of NO and H 2 S, potent gaseous vasodilators in the developing gastrointestinal tract 16 , 27 , 28 , 39 . We demonstrated that inhibition of synthesis of NO abolished the RIC-mediated improvements in intestinal perfusion and resulted in poor intestinal morphology and increased inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that our route of administration for the H 2 S donor was IP. When injecting the compound, H 2 S will diffuse throughout the body [ 26 ] including the intestinal villi [ 36 ] where L-cells are located. Indeed, IP injections of GYY4137 have been previously shown to impact villus structure [ 36 ] suggesting the compounds ability to reach the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, H 2 S exerts both pro-and anti-inflammatory effects [24]. The exogenous hydrogen sulfide donor GYY4137 induces the slow release of H 2 S and reduces intestinal inflammation and protects against intestinal ischemia via eNOS-dependent pathways [25].…”
Section: Introductionmentioning
confidence: 99%